2003
DOI: 10.2337/diacare.26.7.2126
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Skeletal Muscle Oxygen Uptake and Reduced β-Cell Function

Abstract: OBJECTIVE -Studies on insulin sensitivity and insulin secretion in subjects with a familial predisposition for type 2 diabetes mellitus (T2DM) traditionally produce inconsistent results. This may be due to small sample size, subject selection, matching procedures, and perhaps lack of a measure of physical fitness. RESEARCH DESIGN AND METHODS -In the present study, we specifically tested the hypothesis that a family history of T2DM is associated with reduced VO 2max , measured by incremental bicycle ergometry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 31 publications
5
31
0
1
Order By: Relevance
“…If anything, FH+ individuals had adopted healthier food habits than FH− participants. In support of our findings, Thamer et al also showed in a study of young healthy individuals that a family history of diabetes was associated with lower oxygen uptake [11].…”
Section: Discussionsupporting
confidence: 92%
“…If anything, FH+ individuals had adopted healthier food habits than FH− participants. In support of our findings, Thamer et al also showed in a study of young healthy individuals that a family history of diabetes was associated with lower oxygen uptake [11].…”
Section: Discussionsupporting
confidence: 92%
“…We studied 1,469 nondiabetic white subjects (>98% of German ancestry) who participated in the ongoing Tübingen Family Study for type 2 diabetes, which currently includes ~2,000 individuals (16). All participants underwent physical examination, medical history assessment, routine blood tests, and an oral glucose tolerance test (OGTT).…”
Section: Methods and Procedures Subjectsmentioning
confidence: 99%
“…Insulin resistance was determined by two methods; homeostasis model assessment of insulin resistance (HOMA-IR) calculated as the product of the fasting plasma insulin (µU/ml) and the fasting plasma glucose level (mg/dl) divided by 405 and the composite whole-body-insulin-sensitivity index (WBISI) calculated using mean values of insulin (µU/ml) and glucose (mg/dl) obtained from the OGTT and corresponding fasting values [21]. The appropriateness of beta cell function for the individual insulin sensitivity was evaluated by the disposition index, calculated as the product of IGI and WBISI [22][23][24].…”
Section: Calculationsmentioning
confidence: 99%